Plasma cytomegalovirus (CMV) DNA load predicts CMV disease and survival in AIDS patients. - Spector, S A (1998)
In this study, baseline plasma from 619 persons with acquired immunodeficiency syndrome (AIDS) (median CD4+ lymphocyte count -21/microl) who participated in a trial to determine the efficacy of oral ganciclovir for cytomegalovirus (CMV) disease prevention were evaluated for CMV DNA load by qualitative and quantitative polymerase chain reaction (PCR), and correlated with the development of CMV disease and survival. For participants without detectable plasma CMV DNA, the 12-mo Kaplan-Meier CMV disease event rate was 14% and 1% for the placebo and ganciclovir groups, respectively (P < 0.001). For PCR positive participants, CMV disease developed in 43% of placebo and 26% ganciclovir recipients (P < 0.017). Among placebo recipients, CMV PCR positivity was associated with a 3.4-fold increased risk of developing CMV disease (P < 0.001) whereas CD4+ lymphocyte count was not a useful predictor (P = 0.47). A positive plasma CMV DNA PCR was also associated with a 2.5-fold increased risk of death. Each log10 increase in baseline CMV DNA load was associated with a 3.1-fold increase in CMV disease (P < 0.001) and a 2.2-fold increase in mortality (P < 0.001). These data indicate that the risk of developing CMV disease and death in persons with advanced AIDS is directly related to the quantity of CMV DNA in plasma, and is a better predictor than CD4+ lymphocyte count in this population.